The genus Cylloepus Erichson, 1847 (Coleoptera: Elmidae: Elminae) new species and combinations - Polizei, Thiago T. S.; Barclay, Maxwell V. L. (Zootaxa, 2019)
Elmidae is one of the most diverse families of aquatic beetles, with more than 1500 species in 148 genera. Cylloepus is the genus with the most species in Americas, with 52 species and 2 subspecies currently known. The genus is easily recognised by external morphology; body elongate, pronotum with a longitudinal impression on the disc and elytra striate and punctate. In this paper, based on the study of several international reference collections, we propose two new combinations, and describe two new species of Cylloepus (C. bispoi sp. nov. and C. segurae sp. nov.) from Ecuador and Bolivia.